Initiation of swarming in Bacillus subtilis as a resolution for the sorites paradox in bacteria - Ajesh Jose; Shira Omer Bendori; Avigdor Eldar; Daniel B. Kearns; Gil Ariel; Avraham Be’er (Proceedings of the National Academy of Sciences, 2026)
As a single cell grows and multiplies, at what stage does it constitute a swarm? Here, we provide an answer for Bacillus subtilis . We place single planktonic cells onto agar and monitor the biological and physical phases as they transition into an active, swarming cohort. We identify four distinct, nonoverlapping stages enroute to swarming. Using different mutants, we pinpoint the roles of specific cellular processes in the buildup of collective motion. Our results provide a detailed description of the transition from planktonic to a swarming lifestyle—a hallmark of bacterial adaptability to changing environments.